Isolation and Identification of Bacterial Pathogens from Blood Cultures in a Tertiary Care Hospital and Their Clinical Correlation - Satapathy, Dr. Satyaram; Mandavi, Dr. Dhanuram; Panda, Dr. Dhiren Kumar; samal, Dr. Debasish (South Eastern European Journal of Public Health, 2024)
Objective: This study aimed to isolate and identify bacterial pathogens from blood cultures of patients with suspected bloodstream infections (BSIs) in a tertiary care hospital, analyze their antimicrobial susceptibility patterns, and establish clinical correlations. Methods: A cross-sectional study was conducted in the Microbiology Department of a tertiary care hospital. Blood samples from 60 patients were collected aseptically, processed using BACTEC, and cultured on blood and MacConkey agar. Bacterial isolates were identified based on colonial morphology, Gram staining, and biochemical tests. Antibiotic susceptibility testing was performed using the modified Kirby-Bauer disk diffusion method according to Clinical and Laboratory Standards Institute (CLSI) guidelines. Results: The overall culture positivity rate was 26%, with higher positivity among female patients (31.57%) and neonates or infants under six months (26%). Klebsiella pneumoniae was the most frequently isolated pathogen (53.33%), followed by Staphylococcus aureus (20.00%), Escherichia coli (13.33%), and Citrobacter species (13.33%). Klebsiella pneumoniae showed high resistance to ceftazidime and piperacillin, while remaining sensitive to cefoperazone and tobramycin. Staphylococcus aureus isolates were resistant to penicillin and erythromycin but sensitive to vancomycin and cefazolin. The prevalence of multidrug resistance among isolates underscores the need for targeted empirical therapy. Conclusion: Klebsiella pneumoniae emerged as the primary pathogen in BSIs, with significant resistance to commonly prescribed antibiotics. These findings highlight the necessity for enhanced infection control measures, especially in NICUs, and the implementation of local antibiograms to guide effective antibiotic therapy and mitigate resistance trends. Further research across multiple centers is recommended to validate these findings and inform broader clinical guidelines.